Development of Integrated Science E-Learning Materials Integrated with Ethno-PjBL to Encourage Students' 21st Century Skills - Ilma Hayatil Husna; Asrizal (Jurnal Penelitian Pendidikan IPA, 2025)
In the 21st century, students are required to master the 4C skills, including critical thinking, creativity, communication, and collaboration. These four skills are essential so that students are ready to face various complex challenges in the future. To achieve this goal, success is needed in the learning process, including in integrated science learning. One concrete effort to support the success of integrated science learning is through the development of effective teaching materials, especially electronic teaching materials that can be used independently by students. In the context of this study, the product developed is an integrated science e-teaching material integrated with the Project-based Learning (PjBL) model and the ethnoscience context. This e-teaching material is specifically designed to encourage mastery of 21st century skills in grade VIII junior high school students. The e-teaching material was developed using Flip PDF Professional software. The development model used in this study is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). These stages include needs analysis, product design, teaching material development, implementation, and evaluation to ensure product quality. The results of the study indicate that the development of integrated science e-teaching materials that integrate the PjBL and ethnoscience models is proven to be valid and practical for use in learning. The implication of this study is the availability of innovative teaching materials that have great potential to improve students' 21st century skills, in line with the demands of contemporary education. The existence of these e-teaching materials is expected to be a solution in overcoming the 4C skills gap that is still found in students, as well as encouraging a more effective and relevant integrated science learning process.